Attitude towards ageing and perceived health status of community-dwelling older persons in a low resource setting: a rural-urban comparison (2021)
Background: Older person’s attitude to ageing is critical for their adjustment, acceptance of health-related behaviour, survival and choices. Their attitude influences how they cope with the challenges experienced while ageing, which affects their quality of life and health-related outcomes. Despite the increasing number of older persons in sub-Saharan Africa, there is limited information about their experience. This study examines the experience and attitude of older persons in Nigeria regarding the ageing process. Methods: A descriptive cross-sectional study among older persons aged 60 years and above was carried out in a selected rural and an urban community in Oyo State, south-western Nigeria. The study participants were selected using a multi-stage sampling technique. Trained research assistants collected data with the aid of an interviewer administered, semi-structured questionnaire. The Attitude to Ageing Questionnaire (AAQ) was used to measure participants’ perception of ageing in three domains (psychosocial loss, physical changes and psychological growth). Data were analysed using Stata version 14 at a level of significance p < 0.05. Results: A total of 1,180 participants (588 rural vs. 592 urban) were recruited for the study. The mean age was 73.2 ± 9.3 years. The majority (69.7 %) were females and still working (50.5 %). Overall, urban-dwelling participants had a better attitude to the ageing process in all the domains compared with rural-dwelling participants (psychological growth 32.5 ± 3.4 vs. 32.4 ± 3.3, p = 0.30; physical change 27.5 ± 5.1 vs. 26.9 ± 5.0, p = 0.03; and psychosocial loss 25.3 ± 5.7 vs. 25.0 ± 5.3, p = 0.60). Among the rural and urban-dwelling participants, good self-rated health was significantly associated with a positive attitude to ageing across the domains. Conclusions: Older persons residing in urban communities had higher positivity to ageing than their rural older counterparts. The common factor significantly associated with a positive attitude to ageing in both groups was good self-rated health. This information can be used for the planning of targeted interventions and informing policy formation for improved provisions for community-dwelling older persons in Nigeria and other sub-Saharan African countries.